PEMBUATAN TEPUNG BUAH MENGKUDU (MORINDA CITRIFOLIA) SEBAGAI ALTERNATIF BAHAN SUBSTITUSI PRODUK COOKIES DENGAN VARIASI WAKTU DAN SUHU PENGERINGAN MENGGUNAKAN ALAT DEHIDRATOR - Rahmawati, Jenny; Anggorowati, Dwi Ana (jurnal ATMOSPHERE, 2025)
Young noni fruit has a carbohydrate nutrient content of 51.67%, where with the amount of nutrient content, noni fruit can be processed into flour as a food additive so that it functions optimally. The objectives of this study include determining the factors that affect the drying of noni fruit, determining the effect of variations in temperature and drying time on the nutritional content of noni fruit flour and determining the drying rate of noni fruit with a dehydrator dryer. Uses a drying with a Dehydrator, the variables used are temperatures of 50oC, 55oC, 60oC, 65oC, 70oC and times of 4 hours, 5 hours and 6 hours. With the process of selecting raw materials, soaking raw materials, drying noni fruit, then making noni fruit flour. The results of the study showed that it was in accordance with SNI, where the water content in time and temperature variations was below 14.5%, ash content below 0.70%, Escherichia Coli bacteria test 0 CFU / g.